Patient initiated follow-up in cancer patients: A systematic review - Newton, Claire; Beaver, Kinta; Clegg, Andrew (Frontiers in Oncology, 2022)
Background Patient-initiated follow-up (PIFU) is increasingly being implemented for oncology patients, particularly during the COVID-19 pandemic, given the necessary reduction in face-to-face hospital outpatient appointments. We do not know if PIFU has a positive (or negative) impact on overall, or progression free, survival. Objectives To investigate the impact of PIFU on overall survival, progression free survival, patient satisfaction, psychological morbidity, specifically quality of life (QoL) and economic costs compared to hospital follow up (HFU), for any type of cancer. Methods We carried out a systematic review using five electronic databases: MEDLINE, CINAHL, EMBASE, PsycInfo and Cochrane Central Register of Controlled Trials. Studies were eligible if they were controlled clinical trials comparing PIFU with another form of active follow-up. Effectiveness was assessed using the primary outcome of overall survival and secondary outcomes of progression free survival, patient satisfaction, psychological morbidity, QoL and cost effectiveness. Results Eight studies met the inclusion criteria and were included. Only one study included survival as a primary outcome and indicated no significant differences between hospital-based follow-up and PIFU, although not adequately powered to detect a difference in survival. For secondary outcomes, few differences were found between PIFU and other forms of active follow-up. One study reported significant differences in fear of cancer recurrence between PIFU and HFU although did not reach the limit of clinical significance; in the short term, fear decreased significantly more in hospital based follow-up. Conclusion We do not have evidence to support the impact of PIFU on survival or progression free survival. Fully powered randomized controlled trials are required to determine the full impact of PIFU in the longer term.